HUBUNGAN TINGKAT PEMAHAMAN KODE ETIK GURU DENGAN KINERJA GURU PAUD DI KECAMATAN RETEH KABUPATEN INDRAGIRI HILIR - Cahyani, Elita; Novianti, Ria; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is that teachers are required to have a performance that is able to provide the hopes and desires of all parties, especially the general public who have trusted the school and the teacher in fostering students. In improving the performance of the ethics code is one that affects teacher performance.The purpose of this study was to determine the correlation between ethics code comprehension and the work performance in early childhood education teachers in the reteh district of inrdagiri hilir regency. The population in this study were all early childhood educators teachers in Reteh Subdistrict, Indragiri Hilir Regency, which were as many as 72 teachers consisting of 25 early childhood. The sample used is a saturated sample which means the population is sampled. The sample used is a saturated sample which means that the population is sampled. Data collection techniques used were questionnaires and tests. The data analysis technique uses descriptive analysis and product moment correlation analysis which has previously been tested by assumptions. The results of the study indicate that there is a low relationship between understanding the teacher's code of ethics and the performance of PAUD teachers. Obtained a value of r_ (count) of 0.063 with sig 0.598, because sig> 0.05, it can be concluded that there is no significant effect between the understanding of the teacher's code of ethics with PAUD teacher work. In the hypothesis test can be seen r_ (count) = 0.063 rtable = 0.231. It can be interpreted that there is no significant influence between understanding the teacher's code of ethics and the performance of PAUD teachers. The influence of the understanding of the teacher's code of ethics on the performance of PAUD teachers in TK Reteh Indragiri Hilir District by 4%.Key Words: Understanding of ethical codes, teacher performance